The Men of the First French Republic : Political Alignments in the National Convention of 1792 - Patrick, Alison (Book collections on Project MUSE., 1972)
"The French National Convention election elected the National Convention The election was held in September and were the first to be held under universal suffrage. An absolute majority of the deputies elected belonged to the Marais party, a political faction of vague but largely moderate policies. The Montagnards or Jacobins received 200 seats and the republican, though more moderate Girondin faction 160 seats. The election preceded the fall of the Gironde as a political faction, mainly because of the political and social unrest following the war started by the Girondist-dominated government in the spring of 1792. Turnout was only 10%."--Wikipedia.